Mengulik Kitab Tafsir Al-Qur’an Al-Karim Mahmud Yunus - Leni Mardiah (LPPI Universitas Al-Qolam Malang, 2025)
The Qur’anic Exegesis of Mahmud Yunus is one of the most popular Indonesian-language tafsir works among Indonesian Muslims. This article examines the strengths and weaknesses of the tafsir, as well as its relevance in contemporary studies. Its main strengths lie in the use of accessible and easy-to-understand language, a structured method of interpretation, and a scientific approach that links Qur’anic verses with developments in modern knowledge. The contextual approach and the socio-cultural relevance to the Indonesian setting are added values that make it suitable as a practical learning source and introductory reference for the general public in understanding the Qur’an. Moreover, the use of the tahlili method in interpretation presents a verse-by-verse analysis, complete with vocabulary explanations, background of revelation (asbāb al-nuzūl), and scholarly opinions, providing a comprehensive and systematic picture. However, there are several limitations that need to be considered, such as the minimal use of in-depth linguistic analysis, limited exploration of differences in scholarly opinion, and the lack of attention to Sufi and philosophical dimensions. Furthermore, challenges in maintaining accuracy in Indonesian linguistic structure and the possibility of varied interpretations are also notable concerns. Overall, this tafsir serves well as an introductory and practical reference, but may be insufficient for more advanced and in-depth exegetical studies. This research is expected to help readers understand the strengths and limitations of Mahmud Yunus’s tafsir and assess its relevance within the context of modern Islamic studies. Keywords: Mahmud Yunus’s Tafsir, Qur’anic exegesis, scientific approach, strengths and weaknesses, tafsir studies.